(untitled) (Journey for Sustainable Development and Peace Journal, 2024)
Nepal is rich in water resources, and hydropower development has been a key issue for the country’s socio-economic development. But, it needs to produce huge amounts of electricity to support economic activities and growth, though it faces challenges. The paper attempts to fill this gap by studying hydropower development in support of economic growth and overall development, and further discussing its challenges through a literature review analysis and Key Informant Interviews. Economically, Nepal has more than 42000 MW of hydropower generation capacity, but the present generation capacity is 2945 MW, though only below more than 50 percent of the total generation capacity works out in the dry season due to low water discharge and faces a deficiency of electricity. Nepal also imports electricity from India to fulfill domestic demands in the season. There is a gap in the demand and supply lines. Hydropower has become a de-facto reality in light of economic development and the production of hydropower is crucial as Nepal exported electricity of Rs.15.4 billion worth last year. However, this study shows that the prospect of hydropower development is optimistic, though, there are several challenges in terms of priorities of needy projects, investment, environment-forest-land policies, and governance aspects. If pragmatic policy, effective governance, and leadership interventions are adopted on time, challenges can be overcome.